Mesoporous MCM-41 material for hydrogen storage: A short review. (22nd June 2016) - Dündar-Tekkaya, Ezgi; Yürüm, Yuda
Abstract: Decreasing supply of fossil fuels and concerns about environmental issues makes hydrogen a good alternative to fossil fuel sources as it is an environmentally friendly energy carrier. However, the storage of hydrogen is the main challenge to its effective use. For the utilization of hydrogen, the development of safe, effective and high capacity storage media is needed. MCM-41 that is most commonly used in catalytic applications has been also considered for hydrogen storage due to its high surface area, uniform pore size and good adsorption properties. There are a number of researches in which MCM-41 is now also considered as hydrogen storage media with a maximum reported hydrogen uptake of 2.01 wt%. However, there is not any review specifically on the hydrogen storage of MCM-41. Therefore, the present review highlights the recent studies on the use of MCM-41 as hydrogen storage media as well as its synthesis conditions and the effect of loading metal on the storage capacity. Highlights: Hydrogen is one of the best alternatives to fossil fuel sources. Porous materials are good candidates for hydrogen storage. Promising results in gas adsorption of MCM-41 lead to the hydrogen storage studies of the material. The hydrogen storage of MCM-41 was reviewed.